THE IMPLICATURE IN FLOUTING OF MAXIMS FOUND IN THE SIMPSONS MOVIE - DANI, SURYA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cooperative principle, flouting of maxim, implicature, the Simpsons Movie. Language takes an important part in human life. It is considered as a tool for communication. People express their feelings and convey their intention throughcommunication. Good communication will happen if people obey four maxims incooperative principle. However, there is a phenomenon when someone flouts themaxims since they want to imply something. The phenomenon is called implicature that always comes with flouting of maxims. The phenomenon is presented in The Simpsons Movie. There are two research problems of the study, namely: (1) what are the flouted maxims found in “The Simpsons Movie” and (2) what is the most frequent flouting of maxim found in “The Simpsons Movie and What are the possible reasons for the most frequently appears flouted maxim?This study uses qualitative approach in relation to the use of clear description about the phenomena being studied. Document analysis is applied in this study to analyze conversation of the characters through the script of The Simpsons movie.  This study reveals that all floutings of maxims occur in this movie. From the occurrence of all maxims, maxim of manner is flouted most frequently. When this maxim is flouted, the hearer tends to fail to infer the intended meaning conveyed by the speaker due to its obscurity.The writer suggests the next researchers conduct a research in movie which has funny and unique implicature to make interesting analysis and consider the context carefully in analyzing the data to make accurate analysis. Furthermore, the writer also suggests the next researcher make comparison between a study which uses movie as the as the data source to a study which uses other literary works as the data source.